Becoming Citizen Spatial and Expressive Acts when Strangers Move In - Andersen, Peter Kærgaard; Mouritzen, Lasse; Samson, Kristine (2018)
This article examines the conditions and expressions of how refugees in Denmark become citizens. Through visual and collaborative ethnographic fieldwork, which took place during 2017, the case study follows the everyday life of an Eritrean community living in a former retirement home in the town of Hørsholm. The article investigates how becoming citizen can be understood as mediatised, spatial and expressive negotiations between the refugees and the local society. We look at the conditions of becoming citizen through the local framing of the Eritrean community—understood as political, social, cultural and material framing conditions. We draw on Engin Isin’s concept of performative citizenship (Isin, 2017), and we suggest how everyday life and becoming potentially hold the capacity to re-formulate and add to the understanding of citizenship. We suggest that becoming citizen is not merely about obtaining Danish citizenship and civic rights nor tantamount with settling down. On the contrary, the analysis shows that becoming citizen is a process of expressed and performed desires connected to global becomings beyond the sedentary citizenship, and therefore holds capacity for transforming and diversifying the notion of citizenship.
Keywords: Becoming; Citizenship; cultural encounters; Globalisation; performative citizenship